Dielectrophoretic cell trapping for improved surface plasmon resonance imaging sensing. Issue 10 (20th March 2019) - Costella, Marion; Avenas, Quentin; Frénéa‐Robin, Marie; Marchalot, Julien; Bevilacqua, Pascal; Charette, Paul G.; Canva, Michael
Abstract: The performance of conventional surface plasmon resonance (SPR) biosensors can be limited by the diffusion of the target analyte to the sensor surface. This work presents an SPR biosensor that incorporates an active mass‐transport mechanism based on dielectrophoresis and electroosmotic flow to enhance analyte transport to the sensor surface and reduce the time required for detection. Both these phenomena rely on the generation of AC electric fields that can be tailored by shaping the electrodes that also serve as the SPR sensing areas. Numerical simulations of electric field distribution and microparticle trajectories were performed to choose an optimal electrode design. The proposed design improves on previous work combining SPR with DEP by using face‐to‐face electrodes, rather than a planar interdigitated design. Two different top‐bottom electrode designs were experimentally tested to concentrate firstly latex beads and secondly biological cells onto the SPR sensing area. SPR measurements were then performed by varying the target concentrations. The electrohydrodynamic flow enabled efficient concentration of small objects (3 μm beads, yeasts) onto the SPR sensing area, which resulted in an order of magnitude increased SPR response. Negative dielectrophoresis was also used to concentrate HEK293 cells onto the metal electrodes surrounded by insulating areas, where the SPR response was improved by one order of magnitude.